Evaluation of a New Automated Mono-Test for the Detection of Aspergillus Galactomannan: Comparison of Aspergillus Galactomannan Ag VirCLIA® Mono-Test with PlateliaTM Aspergillus Ag ELISA Assay - Giuliana Lo Cascio; Valentina Lepera; Annarita Sorrentino; Domenico Caleca; Paolo Gigante; Gabriella Tocci; Alda Bazaj; Annalisa Mancini; Marina Bolzoni; Evelina Cattadori; Davide Gibellini; Chiara Gorrini; et al. (Journal of Fungi)
The analytical performance of the new Aspergillus Galactomannan Ag VirCLIA® mono-test (Vircell S.L.) was compared to the Platelia™ Aspergillus Ag ELISA assay (Bio-Rad). Prospective serum and bronchoalveolar lavage (BAL) samples from patients at risk of invasive aspergillosis (IA) were tested using both the Aspergillus Galactomannan Ag VirCLIA® mono-test and the Platelia™ Aspergillus Ag ELISA assay. Concordance, sensitivity, specificity, and positive and negative predictive values were calculated using the manufacturer-recommended cutoff levels. Receiver operating characteristic (ROC) analysis and the Youden index were performed to determine the optimal cutoff. A total of 187 serum samples and 73 BAL samples were analyzed with both assays. The concordance between the Aspergillus Galactomannan Ag VirCLIA® mono-test and the Platelia™ Aspergillus Ag ELISA assay was 87.8%, with a Cohen’s kappa of 0.75. The sensitivity and specificity of the Aspergillus Galactomannan Ag VirCLIA® mono-test were 78.6% and 96.2%, respectively, with positive and negative predictive values of 94.8% and 83.3%. The ROC curve for the Aspergillus Galactomannan Ag VirCLIA® mono-test demonstrated an area under the curve (AUC) of 0.87, and the Youden index at the manufacturer’s established cutoff was 0.73. This new Aspergillus Galactomannan Ag VirCLIA® mono-test exhibited adequate analytical and clinical performance, showing good correlation with the Platelia™ Aspergillus Ag ELISA assay. The single-sample, semi-automated test is user-friendly, allowing small laboratories to perform the test on demand without the need for batch evaluations, providing a useful solution for timely diagnostic support for clinicians.